Turning Up the Heat: Local Temperature Control During in vivo Imaging of Immune Cells - Ahl, David; Eriksson, Olle; Sedin, John; Seignez, Cédric; Schwan, Emil; Kreuger, Johan; Christoffersson, Gustaf; Phillipson, Mia (Frontiers in Immunology, 2019)
Intravital imaging is an invaluable tool for studying the expanding range of immune cell functions. Only in vivo can the complex and dynamic behavior of leukocytes and their interactions with their natural microenvironment be observed and quantified. While the capabilities of high-speed, high-resolution confocal and multiphoton microscopes are well documented and steadily improving, other crucial hardware required for intravital imaging is often developed in-house and less commonly published in detail. In this report, we describe a low-cost, multipurpose, and tissue-stabilizing in vivo imaging platform that enables sensing and regulation of local tissue temperature. The effect of tissue temperature on local blood flow and leukocyte migration is demonstrated in muscle and skin. Two different models of vacuum windows are described in this report, however, the design of the vacuum window can easily be adapted to fit different organs and tissues.